So-smart bus stop - Husin, Nor Fatahiah; Jaafar, Jamilah; Mohd Shafie, Muhammad Shafiq Fahmi; Mohd Fadhil, Intan Solehah; Syamsul, Nursyahiera (Universiti Teknologi MARA, Kedah, 2019)
All this while, the passenger are served with uncomfortable and unfriendly bus-stops. They are exposed to all sorts of risks for example the sunlight, the thunder and lightning, the rain pour, even the noise made by the surroundings. If we had the choice, we wouldn't want to wait for the bus to come at this kind of bust stop. It will be inconvenient, uncomfortable and unsafe with the unfriendly bus-stop, we are having now. Due to this, we have come up with this idea, So-Smart Bus Stop. Not only the passengers will feel comfortable, but also they will feel safer and protected. It is because this 'So-Smart Bus Stop' is accomplished with better infrastructure. We have a buildin mini library and information corner where the passengers can read books to gain more knowledge while waiting for the bus to come. The So-Smart Bus Stop is completed with an adjustable roof and transparent wall as the main features. To where the passengers will be protected from direct sunlight, the roof is adjustable to the climate. The wall is made of transparent glass to avoid the rain pour from falling on the passengers and make them and the books soaked-wet. Another special feature about this So-Smart Bus Stop, it has an automatic sensor which can detect darkness to switch on the light, and move the fan when there is any movement entering the bus stop. It also provide the USB ports for charging the gadgets. The power supply is a conversion of solar energy to electricity. It is also provided with 'panic button' that can dial the police station, fire department or hospital if in any case, the passengers have any emergencies.